Dental Biofilm, a reservoir for Helicobacter Pylori in patients with chronic gastritis - Guerra Cuyutupac, Israel Armando (2020)
Objectives: To determine the prevalence of helicobacter pylori in dental biofilm in patients with chronic gastritis in the gastroenterology service of Hospital María Helper. Methods: A cross-sectional descriptive observational study was carried out, working with a population of patients attended in 1 calendar year, of the of which only 100 patients met the inclusion and exclusion criteria. It has been made a collection for the variables age, sex, helicobacter pylori in dental biofilm and helicobacter pylori in gastric mucosa biopsy. The relative frequency of Helicobacter Pylori in dental biofilm in patients with chronic gastritis and so exploratory a chi2-square test was performed for helicobacter in dental biofilm and helicobacter in gastric mucosa biopsy. Results: A prevalence of helicobacter pylori was detected in dental biofilm from 66% in patients with chronic gastritis, in turn 48% of the total in this group I present a positive helicobacter pylori in gastric mucosa biopsy. From the patients positive for helicobacter pylori in gastric mucosa 83.33% presented positivity in dental biofilm. An association was found for the variables helicobacter pylori in dental biofilm and helicobacter pylori in gastric mucosa biopsy with a p value = 0.002. Conclusions: A high prevalence of helicobacter pylori was found in biofilm of patients with chronic gastritis and an association between dental biofilm and gastric mucosa biopsy for helicobacter pylori.